An Optimized Anti-infliximab Bridging Enzyme-linked Immunosorbent Assay for Harmonization of Anti-infliximab Antibody Titers in Patients with Inflammatory Bowel Diseases. Issue 9 (September 2015) - Van Stappen, Thomas; Billiet, Thomas; Vande Casteele, Niels; Compernolle, Griet; Brouwers, Els; Vermeire, Séverine; Gils, Ann
Abstract : Background: The formation of anti-infliximab antibodies (ATI) is associated with loss of response and adverse events in patients with inflammatory bowel diseases, leading to the introduction of ATI monitoring for guiding treatment adjustments. However, a lack of standardization among current available assays exists, hampering comparison of results from different studies. This study aimed to improve the harmonization of clinically validated ATI enzyme-linked immunosorbent assays (ELISAs) by introducing a monoclonal anti-infliximab antibody (MA-IFX). Methods: A panel of MA-IFX was evaluated as calibrator in the first generation ATI ELISA. After selection of 1 MA-IFX, assay conditions were optimized and biotin-streptavidin-enhanced detection of bound infliximab was introduced. The novel second generation ELISA was used for reanalysis of 127 serum samples from a cohort of 12 patients with inflammatory bowel disease, previously identified as ATI positive. Results: Of 55 MA-IFX, MA-IFX10F9 was selected as calibrator in the ATI ELISA. After optimization of the assay conditions, a 4-fold improvement in sensitivity was obtained. Reanalysis of 127 serum samples revealed that in 5 of 12 patients (46%), ATI were detected at least 1 time point earlier with the second generation ELISA compared with the first generation ELISA. In 1 patient, the second generation ELISA allowed to detect ATI before the reinitiation of IFX after a drug holiday. Conclusions: In addition to the improved sensitivity and specificity of the second generation ATI ELISA, MA-IFX10F9 can serve as a universal calibrator to achieve assay harmonization. Moreover, the superiority of the second generation assay in analyzing serum of restarters was demonstrated. Abstract : Article first published online 8 May 2015.